Pemberdayaan Wanita Tani Melalui Budidaya Tanaman Obat Di Kelurahan Pagar Agung Kecamatan Lahat Kabupaten Lahat - Amelia, Dwi; Murdiati, Eni; Isnaini, Mohd Aji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study discusses "Empowering Women Farmers Through Cultivating Medicinal Plants in Pagar Agung Village, Lahat District, Lahat Regency". The purpose of this study was to find out about the empowerment of women farmers and to find out how to cultivate medicinal plants in Pagar Agung Village, Lahat District, Lahat Regency. This study uses qualitative research which is field research, the data collection tools used are interviews, observation and documentation. The subjects of this study were five women members of Bengkurat City Farmers. The data analysis technique used is data reduction, data presentation and conclusion. The results of this study are: 1) Empowerment is an effort made to provide empowerment or strengthening to women farmers as an individual ability related to women farmers which aims to find alternatives in community development. The empowerment of women farmers from this cultivation program is carried out through 4 stages, namely the awareness stage, the capacity building stage, the empowerment stage and the evaluation stage. 2) The cultivation of medicinal plants is carried out so that members can find out about the types of medicinal plants, how to make herbal medicine for body health and the use of medicinal plants as ingredients to treat various diseases in the traditional way. From the existence of empowerment through the cultivation of medicinal plants carried out by these female farmers so that female farmers in the Pagar Agung sub-district can cultivate medicinal plants in their respective yards with the abilities, knowledge and experience they get from the program of female farmers activities.